(untitled) (Research, Society and Development, 2020)
It is about a descriptive research, of well-informed approach that intended to explore black women perspective about the iniquities in the obstetric assistance and analyze their insight about the assistance received during pregnancy, labor and post-partum. Eight women were interviewed, in the period of April to September of 2019, through individual interviews, making use of the open narrative interview technique. The data was analyzed through theme/category-based content analysis technique. Interviewees affirm that they wish for a respectful labor and that is made by their choice, however, they mention their racist experiences lived and strategies used during the pregnancy to escape from obstetric violence. It is concluded that they consider the obstetric assistance scenario as unequal and violent for the black women, making the process of being pregnant and giving birth an escape from violence and a search to ensure a humanized labor. In addition, they claim that the support network is essential for protagonism during childbirth and for black women this network also works as a protective factor in the face obstetric violence.